Pengelolaan Kegiatan Lingkungan Berbasis Partisipatif Sekolah Adiwiyata Di SMP N 6 Salatiga - Sugiyantono, Indri; , Prof. Dr. Sutama, M.Pd; , Dr. Samino, M.M (2015)
The purpose of this research are : (1) to describe the planning management of environmental based participatory of adiwiyata school in SMP 6 Salatiga, (2) to describe the implementation management of environment based participatory of adiwiyata school in SMP 6 Salatiga, (3) to describe the evaluation management of environment based participatory of adiwiyata school in SMP 6 Salatiga. The research type is qualitatif research with etnografi approach. This research is held in SMP 6 Salatiga. The subject of this research are all of school members such as headmaster, teachers, staffs, school committee, and students. The method of data collection are interview, observation and documentation. The analysis data are (1) data collection, (2) data reduction, (3) data display, and (4) conclusion. Data validity uses credibility, transferability, confirmability, and dipendability. The result of this research are (1) The school has done the planning management the activity of environmental based participatory well, (2) The school has done the management the activity of environmental based participatory based on the planning, (3) The school has done the evaluation management the activity of environmental based participatory well. Those have showed by reaching 80% of standart that has established by government.